Successful Multi-Level HPV Vaccination Intervention at a Rural Healthcare Center in the Era of COVID-19 - Kepka, Deanna; Christini, Kaila; McGough, Emily; Wagner, Anna; Del Fiol, Guilherme; Gibson, Bryan; Ayres, Shauna; Brandt, Heather M.; Mann, Sara; Petrik, Amanda F.; Coronado, Gloria D. (Frontiers in Digital Health, 2021)
Objectives: To develop and test a human papillomavirus (HPV) vaccination intervention that includes healthcare team training activities and patient reminders to reduce missed opportunities and improve rates of appointment scheduling for HPV vaccination in a rural medical clinic in the United States. Methods: The multi-level and multi-component intervention included healthcare team training activities and the distribution of patient education materials along with technology-based patient HPV vaccination reminders for parents/caregivers and young adult patients. Missed vaccination opportunities were assessed pre- and post-intervention (n=402 and n=99 respectively) by retrospective chart review and compared using Pearson χ2. The patient parent/caregiver and young adult patient population (n=80) was surveyed following the reminder messages and penalized logistic regression quantified unadjusted odds of scheduling a visit. Results: Missed opportunities for HPV vaccination declined significantly from the pre-intervention to the post-intervention period (21.6% vs. 8.1%, respectively, p-value=0.002). Participants who recalled receipt of a vaccination reminder had a 7.0 (95% CI 2.4-22.8) higher unadjusted odds of scheduling a visit compared with those who did not recall receiving a reminder. The unadjusted odds of confirming that they had scheduled or were intending to schedule a follow-up appointment to receive the HPV vaccine was 4.9 (95% CI 1.51-20.59) times greater among those who had not received the vaccine for themselves or for their child. Conclusions: Results from this intervention are promising and suggest that vaccination interventions consisting of provider and support staff education and parent/caregiver and patient education materials and reminders can reduce missed opportunities for vaccinations in rural settings.